PENGARUH BUAH LEMON SEBAGAI MEDIA PEMBELAJARAN LISTRIK DINAMIS TERHADAP KONDISI STRESS BELAJAR SISWA - Ulya Santa Anugrahaini; Sutikno Sutikno; Masturi Masturi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Fruit is not only as a source of vitamins that are beneficial to health. Energy experts begin to look for the existence of the fruit that is not just a complement of nutrients; they open a new knowledge that the fruit can become a source of electrical energy alternatives. On the other hand, the educators participating improve the usefulness of the fruit in learning activities as a learning medium dynamic power which can help students and teachers in achieving the learning objectives. In this study, the fruit is used as a medium of electrodynamic power which can reduce students' stress conditions. This student learning stress conditions will affect the memory, memory, concentration and student achievement. The purpose of this study is to determine the effect of lemon as a medium of learning to learn physics student stress conditions, so that the results of this study indicates that the fruit is not only capable of as a source of vitamins and alternative electric energy source, but it can be useful as a learning medium which can reduce student’s stress conditions. Keywords: Lemon, Stress Conditions of Students Learning, Electrodynamics Learning Media.